2007
DOI: 10.1249/01.mss.0000240328.31276.fc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hiking Downhill Using Trekking Poles while Carrying External Loads

Abstract: A reduction in the forces, moments, and power around the joint, with the use of poles, will help reduce the loading on the joints of the lower extremity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 16 publications
1
26
1
Order By: Relevance
“…The results of the present study indicated that compared with regular walking, walking with Nordic poles can prevent damage to the lower extremity joints18 ) and relatively reduce loads on the knee joints6 ) . Unlike regular walking exercises, Nordic pole walking exercises induces the mobilization of all upper and lower extremity muscles because poles are used, and so they show higher oxygen consumption by the body compared with regular walking19 ) .…”
Section: Discussionmentioning
confidence: 63%
“…The results of the present study indicated that compared with regular walking, walking with Nordic poles can prevent damage to the lower extremity joints18 ) and relatively reduce loads on the knee joints6 ) . Unlike regular walking exercises, Nordic pole walking exercises induces the mobilization of all upper and lower extremity muscles because poles are used, and so they show higher oxygen consumption by the body compared with regular walking19 ) .…”
Section: Discussionmentioning
confidence: 63%
“…At a given walking speed, NW involves more muscles in various body segments and induces greater exercise intensity compared with level walking (LW) [2-11]. Furthermore, NW places a smaller load on the legs during walking [12-16]. Thus, NW is a considered a good sport for improving health.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding downhill walking, NW does appear to provide benefits. Bohne and Abendroth-Smith (2007) examined the effects of hiking downhill using trekking poles while carrying external loads. They observed a…”
mentioning
confidence: 99%